2017
DOI: 10.1002/ijch.201700099
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Hydrophenylation of Ethylene Using a Cationic Ru(II) Catalyst: Styrene Production with Ethylene as the Oxidant

Abstract: The complex [(MeOTTM)Ru(P(OCH2)3CEt)(NCMe)Ph][BAr′4] (MeOTMM=4,4’,4’’‐(methoxymethanetriyl)‐tris(1‐benzyl‐1H‐1,2,3‐triazole), BAr′4=tetrakis[3,5‐bis(trifluoromethyl)phenyl]borate) is used to catalyze the hydrophenylation of ethylene to produce styrene and ethylbenzene. The selectivity of styrene versus ethylbenzene varies as a function of ethylene pressure, and replacing the MeOTTM ligand with tris(1‐phenyl‐1H‐1,2,3‐triazol‐4‐yl)methanol reduces the selectivity toward styrene. For styrene production ethylene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“… We reported the cationic Ru­(II) complex [(MeOTTM)­Ru­(P­(OCH 2 ) 3 CEt)­(NCMe)­Ph]­[BAr′ 4 ] ( 7 ; MeOTMM = 4,4′,4″-(methoxymethanetriyl)­tris­(1-benzyl-1 H -1,2,3-triazole)) for benzene ethenylation that affords 53 TOs of styrene after 4 h at 150 °C with ethylene serving as the oxidant (Scheme ). Also, our group has disclosed a series of studies using Rh catalysts (Scheme ). Notable features of these reactions include (1) the use of Cu­(II) oxidants, for which we have demonstrated regeneration by dioxygen from air, ,, (2) the conversion of electron-deficient arenes, and (3) the selective formation of anti-Markovnikov addition products, 1-arylalkenes, with a >8/1 anti-Markovnikov/Markovnikov ratio in most reactions and higher selectivity under some conditions. ,, In an extension of Rh-catalyzed arene alkenylation, we recently reported oxidative conversion of unactivated arenes and alkenes to alkenylarenes using unpurified air or O 2 as the sole oxidant .…”
Section: Introductionmentioning
confidence: 99%
“… We reported the cationic Ru­(II) complex [(MeOTTM)­Ru­(P­(OCH 2 ) 3 CEt)­(NCMe)­Ph]­[BAr′ 4 ] ( 7 ; MeOTMM = 4,4′,4″-(methoxymethanetriyl)­tris­(1-benzyl-1 H -1,2,3-triazole)) for benzene ethenylation that affords 53 TOs of styrene after 4 h at 150 °C with ethylene serving as the oxidant (Scheme ). Also, our group has disclosed a series of studies using Rh catalysts (Scheme ). Notable features of these reactions include (1) the use of Cu­(II) oxidants, for which we have demonstrated regeneration by dioxygen from air, ,, (2) the conversion of electron-deficient arenes, and (3) the selective formation of anti-Markovnikov addition products, 1-arylalkenes, with a >8/1 anti-Markovnikov/Markovnikov ratio in most reactions and higher selectivity under some conditions. ,, In an extension of Rh-catalyzed arene alkenylation, we recently reported oxidative conversion of unactivated arenes and alkenes to alkenylarenes using unpurified air or O 2 as the sole oxidant .…”
Section: Introductionmentioning
confidence: 99%
“…Arene alkyl- and alkenylation provide an opportunity to affect more atom-economical formation of carbon–carbon bonds between inexpensive arenes and alkenes through undirected C–H activation (Figure b). It has been reported that Ni, , Ru, Pt, , and Ir complexes catalyze olefin hydroarylation (nonoxidative) to produce saturated alkyl arenes, and Pd and Rh catalyze oxidative arene alkenylation using oxidants in many cases with functionalized olefins. We envisioned a strategy in which the reaction between arenes and styrenes in the presence of a rhodium catalyst precursor would form stilbene products through a rhodium-mediated C–H activation followed by vinyl arene insertion, β-hydride elimination, and catalyst regeneration by an air-recyclable copper­(II) oxidant (Figure c).…”
Section: Introductionmentioning
confidence: 99%
“…remains challenging with regard to selectivity, reaction rate, and catalyst longevity. Examples of transition metal-based catalysts for arene alkylation of simple hydrocarbon substrates include Pt, Ru, and Ir. In addition, catalytic oxidative arene alkenylation using Rh and Pd precursors has been reported. …”
Section: Introductionmentioning
confidence: 99%